TEACHERS EDUCATIVE WORK OF PHYSICAL EDUCATION IN THE CONSTRUCTION OF SCHOOL ACTIVITIES: PRACTICAL ACTIVITY OF CORPORAL CULTURE AS AN EXPRESSION OF HUMAN FREEDOM. (Fiep Bulletin - online, 2011)
This article has its genesis inside the State School in Presidente Prudente.SP and it is related a research-intervention in physical Education. The work has been done in the attempt to ensure the school's collective objective conditions of discussion, reflection and realization of practical activities. Therefore, this work try to understand the school as a space that can enable via critical educational work, the development of individuals omnilateral perspective in order to facilitate the development of their motor skills, psychological, emotional, cognitive and social aspects, to get the higher spheres of development at this historic moment. In order to achieve these objectives have been developed in physical education classes and by a group of teachers and students some activities to emphasize group work and the construction of universal ethical values as respect, solidarity, cooperation, freedom and justice. We believe that to understand this kind of education is necessary to consider the role of ontological and emancipating education from a critical perspective. By this kind of work it is possible to overcome the forms of being and acting ideological inside the school and in this way it is possible to build new possibilities for human being and its freedom, overcoming the alienation and individualistic society.
Keywords: School Physical Education; Critical Education Theory; Historical-cultural perspective